2021
DOI: 10.1088/1755-1315/694/1/012058
|View full text |Cite
|
Sign up to set email alerts
|

Agroforestry inside oil palm plantation for enhancing biodiversity-based ecosystem functions

Abstract: At the oil palm landscape, conserving biodiversity and ecosystem processes can range from continuous adjacent forest remnant to tree patches (agroforestry) maintained within the oil palm landscape on steep slopes and riparian margins. The objective of the research was to analyze patched of tree planting inside monoculture oil palm plantation (agroforestry) as one variant of landscape multifunctionality for enhancing biodiversity-based ecosystem functions including soil macrofauna, soil water recharge/retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Several studies have found that agroforestry increases the diversity and abundance of insect pollinators, and thus pollination services (Bentrup et al, 2019;Centeno-Alvarado et al, 2023;Varah et al, 2020). At the same time, other studies found that agroforestry did not affect pollinator diversity (Knowlton et al, 2019;Tarigan et al, 2021) and occasionally had lower pollinator abundance than conventional agriculture (Galbraith et al, 2020). Our results support the argument that agroforestry benefits insect pollinators and thus improves pollination services.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Several studies have found that agroforestry increases the diversity and abundance of insect pollinators, and thus pollination services (Bentrup et al, 2019;Centeno-Alvarado et al, 2023;Varah et al, 2020). At the same time, other studies found that agroforestry did not affect pollinator diversity (Knowlton et al, 2019;Tarigan et al, 2021) and occasionally had lower pollinator abundance than conventional agriculture (Galbraith et al, 2020). Our results support the argument that agroforestry benefits insect pollinators and thus improves pollination services.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have shown that agroforestry increases the diversity and abundance of insect pollinators, because it offers more food and nesting resources for insect pollinators (Hoehn et al., 2010; Silva Neto et al., 2021; Varah et al., 2020). At the same time, other studies found no effect of agroforestry on pollinator diversity (Knowlton et al., 2019; Tarigan et al., 2021) and occasionally even a lower pollinator abundance than conventional agriculture (Galbraith et al., 2020). Most studies predicting the impact of agroforestry on insect pollinators have been conducted in temperate Europe and America (Centeno‐Alvarado et al., 2023; Timberlake & Morgan, 2018), which is unlikely to be globally representative and leaves the impact of agroforests in tropical East Africa largely unknown.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations